Results of Clinical Trials of the First Russian 4-valent Flu Vaccine - D. A. Lioznov (Эпидемиология и вакцинопрофилактика)
Ways for vaccines improvment are described. WHO criteria and domestic requirements for influenza vaccines quality are presented. The multicenter, double-blind, randomized trial in parallel groups of the first Russian quadrivalent vaccine is described in details. Multicenter study for assessment of vaccine safety, reactogenicity and immunogenicity was performed in 612 volunteers aged 18-60 years in the epidemic season 2016-2017.. In the study conducted , it was demonstrated that the first Russian quadrivalent influenza vaccine has a high tolerability and safety profile and meets the criteria for the immunogenicity of inactivated influenza vaccines.